Chemopreventive Effects of Cranberry Extracts on Colitis-Associated Colon Cancer. (29th May 2020) - Wu, Xian; Xue, Liang; Tata, Anuradha; Song, Mingyue; Neto, Catherine; Xiao, Hang
Abstract: Objectives: Colon cancer is the third most common cancer in the U.S., and inflammatory bowel disease (IBD) patients are at a greater risk of developing colon carcinoma. Cranberries ( Vaccinium macrocarpon ) are a commonly grown crop in North America which contain constituents relevant to human health, including flavonoids, phenolics and terpenoids. Recently, we have demonstrated the chemopreventive effects of whole cranberry fruits against colitis and colon cancer in murine models. However, the secondary metabolites in cranberry fruit could play different contributions against colon carcinogenesis. Thus, comparing nonpolar (ECE) and polar extracts (DPE) of cranberries to determine their efficacy on colon carcinogenesis is desired. Methods: Selected polyphenols and other constituents were determined using established methods: quantitative 1H NMR methods by Bruker Assure-RMS for triterpenoids, HPLC-DAD for anthocyanins and flavonol glycosides and proanthocyanidins by DMAC assay. Over half of ECE was made up of triterpenes and sterols and trace amount of proanthocyanidins. Over 70% of DPE was polyphenol and trace amount of triterpenes. Higher free-radical scavenging activity was found in DPE than ECE. Results: Next, we determined the chemopreventive effects of ECE and DPE extracts against colitis-associated colon cancer in azoxymethane (AOM) and dextran sulfate sodium (DSS)-treated mice. It was observed that oral administration of ECE and DPE extracts at physiologically achievable doses significantly suppressed the development of colitis-associated colon cancer, evidenced by decreased tumor incidence, multiplicity and burden, compared to the control group, while minimum side-effect was observed. ECE treatment also reversed the shortening of colon caused by colitis. qRT-PCR results showed that gene expression levels of proinflammatory cytokines IL-1, IL-6 and TNF-α were significantly attenuated by ECE and DPE interventions, in comparison to the control group. Conclusions: In conclusion, our findings demonstrate that the novel cranberry extracts may offer an efficacious, safe and inexpensive means to prevent colonic tumorigenesis in humans, particularly for individuals with chronic inflammation. Funding Sources: USDA-NIFA, Leo and Anne Albert Charitable Trust, UMass Cranberry Health Research Center/UMass President's S&T Initiative, and NIH.